Perancangan Produk Celana Dalam (Underwear) Pria Jenis Brief dengan Penambahan Joint Menggunakan Metode Quality Function Deployment (QFD) - Gidion Karo Karo Gurusinga; Ferry Dian Putra Wijaya (Universitas Bunda Mulia, 2018)
This paper discussed modification of men’s brief underwear which already exists in the market. The modification allowed to change the sectional design of brief underwear into modular form. In the process of modification, the additional component is required for the joint component where the joint component sewed to the waist section of the underwear both left and right. The method would use in this paper are Quality Function Deployment (QFD) and House of Quality (HOQ). Modified products are provided with additional hook and eye-type components, commonly found on women's bra. The additional components increase the total price to be paid for a modified product of Rp 26,000 per unit.